To simplify the expression \( (194)^9 \) using the Power Rule of Exponents, we apply the rule which states that \( (a^m)^n = a^{m \cdot n} \).
First, let's factor \( 194 \):
\[ 194 = 2 \times 97 \]
Now we can express \( (194)^9 \) as:
\[ (194)^9 = ((2 \times 97)^1)^9 \]
Using the Power Rule, we rewrite it:
\[ (194)^9 = 2^9 \times 97^9 \]
Thus, the simplified equivalent expression for \( (194)^9 \) is:
\[ 2^9 \times 97^9 \]
This can also be written as:
\[ (2 \times 97)^9 = 194^9 \]
However, since the expression \( 194^9 \) is the original form, the simplified form remains \( 2^9 \times 97^9 \) for clarity.
So, the final answer is:
\[ 2^9 \times 97^9 \]